Screening of the Reissner-Nordstrom charge by a thin-shell of dust matter - Mazharimousavi, S. Habib; Halilsoy, M. (Springer, 2015)
A concentric charged thin-shell encircling a Reissner-Nordstrom black hole screens the electric/magnetic charge completely to match with an external Schwarzschild black hole. The negative mass thin-shell is shown to be stable against radial perturbations. It is shown further that by reversing the roles of inside Reissner-Nordstrom and outside Schwarzschild geometries the mass of the appropriate shell becomes positive.
Keywords: Black-Hole; Stability Analysis